Effect of Plant Density on Wheat Stem Sawfly Sex Ratio - Cárcamo, Héctor; Beres, Brian; Wu, Xiuhua; Larson, Tracy; Schwinghamer, Timothy (Frontiers in Agronomy, 2020)
The wheat stem sawfly (Cephus cinctus Norton) has plagued wheat production for over a century in North America. Host plant resistance in the form of wheat cultivars with a solid pith is a key management strategy. In this study we assessed the interaction of plant density, stem thickness and sawfly sex allocation using the most recent bread wheat cultivar with the resistant trait registered in Canada. The resistant cultivar with the solid stem trait was Lillian and it was compared to triticale and Go wheat, both of which lacked this trait. We confined one meter square crop plots using cages and half of the area in some cages was thinned manually to obtain thicker stems. We hypothesized that plant densities would affect stem diameters and solid pith expression, and these would affect host choices by the sawfly and sex ratio allocations. Our data showed that stems with a thicker diameter consistently produced more females compared to thinner stems that were more likely to produce males regardless of wheat cultivar. Shifting the plant population to lower average stem diameters in the resistant cultivar Lillian resulted in a male biased sex ratio, but not consistently. Further field studies are needed to test the hypothesis that at low plant densities of a resistant cultivar, the sex ratio would be more even due to higher female mortality in thicker stems.